(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine effects of 1800 MHz magnetic field on amout of colonic Bactroides and Fusobacterium and colon pathology in rats and determination of KRAS and p53 gene mutation in colon. Materials and Methods: In the present study, three groups were prepared as control, sham and RFR. The RFR group rats were exposed to 1800 MHz GSM-like RFR for 12 weeks as 45 minutes per day. An electromagnetic energy generator was used to generate 1800 MHz RF radiation in the RFR group. At the end of experiments, colons were dissected from rats for histopathological examination and determination of KRAS and p53 mutations. Fecal speciments were collected for bacterial detection. DNA was isolated from fecal bacterias and colon. Results: No differences were observed between sham and control groups, histopathologically. Corrupted gland structure, mucosal edema and inflammatory cell infiltration were observed at mucosal epithelum in the RFR group. An increase in the amount of collagen and fibrosis were detected in the electromagnetic field group. Number of goblet cells showed a statistically significant decrease in electromagnetic field group compared to both the control and sham groups (P<0.05). The increase in the amount of Fusobacterium it was significantly higher in the RFR group compared to the control group. In the quantity of Bacteroides, no differences were observed between the groups. KRAS and Tp53 mutation analysis of all samples were found to be wild type, at the colon tissues. No significant difference observed between the control group and the electromagnetic field treated group. Conclusion: These results support, for 12 weeks 45 min/day exposure to GSM-like RFR caused histopathological damage in rat colon. Also, the amount of Fusobacterium is increased. But RFR exposure did not caused to KRAS and P53 mutations in colon tissue.